2020
DOI: 10.1192/j.eurpsy.2020.30
|View full text |Cite
|
Sign up to set email alerts
|

The link between formal thought disorder and social functioning in schizophrenia: A meta-analysis

Abstract: Background. Formal thought disorder (FTD) and social functioning impairments are core symptoms of schizophrenia. Although both have been observed for over a century, the strength of the relationship between FTD and social functioning remains unclear. Furthermore, a variety of methodological approaches have been used to assess these constructs—which may contribute to inconsistency in reported associations. This meta-analysis aimed to: (a) systematically test the relationship between FTD and social function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 89 publications
1
18
0
Order By: Relevance
“…Nonetheless, same explanation may not hold true for our result on relationship between symptoms and pragmatic discourse failure. In a similar vein, although the close relation between social impairment of schizophrenia and speech disorder is well-documented, outcomes have been mainly obtained as a by-product of formal thought de cit (Marggraf et al, 2020). We con rm and extend existing literature by showing signi cant association between SF and impaired pragmatic linguistic pro le of SCH.…”
Section: Verbal Communicationsupporting
confidence: 77%
“…Nonetheless, same explanation may not hold true for our result on relationship between symptoms and pragmatic discourse failure. In a similar vein, although the close relation between social impairment of schizophrenia and speech disorder is well-documented, outcomes have been mainly obtained as a by-product of formal thought de cit (Marggraf et al, 2020). We con rm and extend existing literature by showing signi cant association between SF and impaired pragmatic linguistic pro le of SCH.…”
Section: Verbal Communicationsupporting
confidence: 77%
“…Despite this strong linguistic dependency of the construct of schizophrenia, not every patient diagnosed with this illness displays a detectable speech disturbance (Roche et al, 2015;Kircher et al, 2018;Oomen et al, 2022). It is important to identify patients who are most likely to be afflicted in the language domain, as speech disturbances directly affect the educational and occupational success (Palaniyappan et al, 2019), interpersonal (Tan et al, 2014) and social functioning (Marggraf et al, 2020) as well as endured stigma (Penn et al, 2000). Identification of this subgroup may assist in prognostication in schizophrenia, as well as making early and targeted interventions for a group that may have higher educational and vocational needs possible, before they manifest significant deficits in these domains.…”
Section: Introductionmentioning
confidence: 99%
“…Eating, grooming, and bathing are basic activities necessary for living in any environment, and even if the patient is discharged from the hospital to a group home, it is expected that these activities can be performed independently or with supervision. Comprehension, expression, and memory require thinking that involves meaningful words, and it has also been suggested that thought disorder leads to social limitations 20) . These results suggest that the degree of disability in self-care, communication, and memory at the start of physiotherapy may be a predictor of whether a patient will be discharged.…”
Section: Discussionmentioning
confidence: 99%